FAWÃ‚TIá¸¤ AL-SUWAR DAN MUNÃ‚SABAH DALAM ALQURAN; Ragam, Kaitan dengan Pesan Surat, dan Nilai-nilai Pendidikannya - Fu`ad Arif Noor (UIN Siber Syekh Nurjati Cirebon, 2020)
Educational values incorporated in Fawa>tih al-Suwar are as tanbi>h (warnings) and guidelines for life, as knowledge embracing many secrets of Allah SWT that cannot be known, as a motivation to always seek knowledge and be taqarrub to Allah Swt, and as a doubt dissolver about Quran, especially for Muslims who are weak in faith because they are influenced by the words of the enemies of Islam which state that the Quran is the product of the Prophet Muhammad SAW. The presence of munasabah that understands the correlation between verses or surahs in Quran certainly has good wisdoms in developing education. Thus, the concept of munasabah is a critical way of examining the interrelationships between verses or between surahs in Quran.Â